TANTANGAN RENCANA PENDIDIKAN DI ERA DISRUPSI - Sahniarti; Sirozi, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
As times progress, technology continues to bring changes to life, particularly in the field of education, which will constantly evolve. Educational planning in the era of disruption faces significant challenges due to the rapid and dynamic advancement of technology. Disruption, marked by digital technological progress, global economic changes, and shifts in labor market demands, has fundamentally altered the educational landscape. The main challenges in educational planning include adapting curricula to be relevant to the needs of Industry 4.0, improving digital literacy, and developing critical and creative thinking skills. Additionally, ensuring the sustainability of the education system in responding to rapid changes is a challenge, especially regarding the gap in access to technology across different regions. On the other hand, educational planning must also consider the challenges related to the changing learning behaviors of students, who are increasingly dependent on technology, as well as the importance of strengthening the role of educators in facing these changes. Therefore, educational planning in the era of disruption requires an adaptive, innovative, and future-oriented approach to ensure that the education system remains relevant and inclusive in addressing global challenges.